Proceedings of the International Symposium on Accelerated Cooling of Rolled Steel, Winnipeg, Canada, August 24-25, 1987 - Ruddle, G. E.; Crawley, A. F. (Proceedings of the Metallurgical Society of the Canadian Institute of Mining and Metallurgy, 1988)
This volume contains 27 papers covering the advances being made in the field of accelerated cooling technology for hot-rolled steel products. Main topics covered include accelerated cooling applications to plate, strip, bars and shapes; system design; process modelling and effects on transformation; microstucture and mechanical properties, providing international steel industry R & D personnel and metallurgical research groups with a state-of-the-art update of this rapidly developing technology.